1990
DOI: 10.1111/j.1745-4530.1990.tb00044.x
|View full text |Cite
|
Sign up to set email alerts
|

THE COMPACTION PROPERTIES of DEHYDRATED POTATO

Abstract: The compaction behavior of two dehydrated potato granule materials has been studied in a cylindrical geometry. the effect of moisture content and the addition of dehydrated potato flake and potato starches has also been considered. the coefficient of friction and the stress anisotropy factor have been calculated from the pressure transmission measurements using a semi‐particulate analysis previously used for polymer powders. the two granule types behaved more similarly under those conditions than their Brabend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…will increase with decreasing height of the compact (equation 3) and the latter that this ratio will increase with decreasing initial height of the compact (prior to compaction). Previous studies with polymer powders [ 171, potato granules [18] and sucrose and sodium chloride [19] have shown the pressure ratio to be relatively insensitive to the changing height during compaction. The results for potato starch are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…will increase with decreasing height of the compact (equation 3) and the latter that this ratio will increase with decreasing initial height of the compact (prior to compaction). Previous studies with polymer powders [ 171, potato granules [18] and sucrose and sodium chloride [19] have shown the pressure ratio to be relatively insensitive to the changing height during compaction. The results for potato starch are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Cereal grains and dehydrated potato are generally used as the major raw materials in extruded snack foods due to their good expansion characteristics (Ferdinand et al, 1990;Christofides et al, 2004;Ìbanoglu et al, 2006). Many researchers have studied the extrusion behavior of potato starch and potato flours/granule (Mackey et al, 1989;Ferdinand et al, 1990;Della Valle et al, 1995;Borba et al, 2005;Singh et al, 2009;Butrim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the extrusion behavior of potato starch and potato flours/granule (Mackey et al, 1989;Ferdinand et al, 1990;Della Valle et al, 1995;Borba et al, 2005;Singh et al, 2009;Butrim et al, 2009). Faller and Heymann (1996) carried out descriptive sensory evaluation of extrudates from potato flakes and potato flour and concluded that the moisture content was the most important variable in determining the overall sensory properties but the effect of potato granule type was insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Compaction principles have been reviewed by Nedderman (1982). A number of compaction test methods have been used for metal (Heckel, 1961), food (Ferdinand et al 1990), agricultural (Mohsenin, 1970), synthetic polymer (Hytm and Spalding, 1990) and pharmaceutical (Kaji et al, 1985, Roberts andRowe, 1987) powders and granular materials. The data may be presented as the applied pressure vs the apparent compact density, the latter often being derived from the piston displacement for a material constrained in a cavity.…”
Section: Introductionmentioning
confidence: 99%